Home design modification for DIY (Do-It-Yourself) installation of inspection pit in the car porch / Noor Azam Yahaya, Mohamad Hamdan Othman, Ezzat Fahmi Ahmad - Yahaya, Noor Azam; Othman, Mohamad Hamdan; Ahmad, Ezzat Fahmi (2022)
The high cost of living and economic downturn can lead to a financial crisis and increase the burglary crime rate. Expensive house prices and shrinking house sizes can increase the stress level of people who live in the city. To deal with the challenging economic environment, creativity plays a major role in helping people to be more productive and effective in their daily lives. DIY activities are one of the alternatives which can increase knowledge and develop skills for economic benefits. The cost-saving activity may positively reduce the impact of the cost of living. Introducing an inspection pit at the terrace houses' car porch area may encourage house owners to practice DIY activities in car maintenance without paying the professionals. Besides, proper modification and dimension of the trench give the advantage of safe storage space to combat the problem of burglary and limited indoor space of typical Malaysian residential buildings in the urban area. A mild steel plate covers the inspection pit to avoid falling into the trench and create defensible space to prevent burglary when the trench is used as storage. It improves home security and offers households, options for dealing with current issues. In conclusion, home design should focus on and promote a sustainable way of life rather than just a shelter.